The relationship between employee well-being and employee performance in banking sector at Kluang, Johor / Hamirah Nadirah Hamdan - Hamdan, Hamirah Nadirah (Faculty of Business and Management, 2018)
Employee well-being had been greatest concern on the global company nowadays despite their competitiveness in increasing productivity and profitability. The importance of employees’ well-being lies in both its relationship to employee performance as it is a crucial component of healthy organizations. High-performing organizations demonstrate greater performance level among their employees. Therefore, the purpose of this research was to investigate the relationships between employees’ well-being (psychological well-being, social well-being and health well-being) and performance among employees of banking sector in Kluang, Johor. This research was quantitative research which distributed using self-administered questionnaires as instruments to collect data. The data collected was evaluated by using Statistical Package for the Social Science (SPSS) Version 23 Software. Multiple Regression Analysis indicates that there were significant relationship between psychological well-being and social well-being towards employee performance. However, there is no significant relationship between health well-being and employee performance.